Laser‐Fabricated 2D Molybdenum Disulfide Electronic Sensor Arrays for Rapid, Low‐Cost, Ultrasensitive Detection of Influenza A and SARS‐Cov‐2. Issue 18 (7th March 2022) - Muratore, Christopher; Muratore, Melani K.; Austin, Drake R.; Miesle, Paige; Benton, Anna K.; Beagle, Lucas K.; Motala, Michael J.; Moore, David C.; Slocik, Joseph M.; Brothers, Michael C.; Kim, Steve S.; Krupa, Kristen; et al.
Abstract: Multiplex electronic antigen sensors for detection of SARS‐Cov‐2 spike glycoproteins and hemagglutinin from influenza A are fabricated using scalable processes for straightforward transition to economical mass‐production. The sensors utilize the sensitivity and surface chemistry of a 2D MoS2 transducer for attachment of antibody fragments in a conformation favorable for antigen binding with no need for additional linker molecules. To make the devices, ultra‐thin layers (3 nm) of amorphous MoS2 are sputtered over pre‐patterned metal electrical contacts on a glass chip at room temperature. The amorphous MoS2 is then laser annealed to create an array of semiconducting 2H‐MoS2 transducer regions between metal contacts. The semiconducting crystalline MoS2 region is functionalized with monoclonal antibody fragments complementary to either SARS‐CoV‐2 S1 spike protein or influenza A hemagglutinin. Quartz crystal microbalance experiments indicate strong binding and maintenance of antigen avidity for antibody fragments bound to MoS2 . Electrical resistance measurements of sensors exposed to antigen concentrations ranging from 2–20 000 pg mL −1 reveal selective responses. Sensor architecture is adjusted to produce an array of sensors on a single chip suited for detection of analyte concentrations spanning six orders of magnitude from pg mL −1 to µg mL −1 . Abstract : A scalable process is developed for integration of 2D MoS2 films as transducer materials for electronic pathogen sensor arrays. The process enables control of sulfur defect density on the MoS2 transducers, enabling control of antibody fragment binding density. Laser‐based processing also allows for control of sensor geometry and architecture to expand dynamic range over six orders of magnitude.